The Effect of Growth and Inequality in Incomes on Health Inequality: Theory and Empirical Evidence from the European Panel - Tom Van Ourti; Eddy Van Doorslaer; Xander Koolman (Tinbergen Institute, 2006)
Europe aims at combining income growth with improvements in social cohesion as measured by income and health inequalities. We show that, theoretically, both aims can be reconciled only under very specific conditions concerning the type of growth and the income responsiveness of health. We investigate whether these conditions held in Europe in the nineties using panel data from the European Community Household Panel surveys. We use pooled interval regressions and inequality decompositions to demonstrate that (i) in all countries except Austria, the income elasticity of health is positive and increases with income, and (ii) that income growth was not pro-rich in most EU countries, resulting in little or no reductions in income inequality and modest increases in income-related health inequality in the majority of countries.Keywords:income inequality, health inequality, income elasticity of health, Europe.Classification-JEL: D30, D31, I10, I12.
Keywords: D30; D31; I10; I12; 330; income inequality; health inequality; income elasticity of health; Europe